The Sexual Politics of Empire - Durban, Erin L. (University of Illinois Press, 2024)
Winner in the LAMMY Awards – Lambda Literary Awards, LGBTQ+ Studies category Evangelical Christians and members of the global LGBTQI human rights movement have vied for influence in Haiti since the 2010 earthquake. Each side accuses the other of serving foreign interests. Yet each proposes future foreign interventions on behalf of their respective causes despite the country’s traumatic past with European colonialism and American imperialism. As Erin L. Durban shows, two discourses dominate discussions of intervention. One maintains imperialist notions of a backward Haiti so riddled with cultural deficiencies that foreign supervision is necessary to overcome Haitians’ resistance to progress. The other sees Haiti as a modern but failed state that exists only through its capacity for violence, including homophobia. In the context of these competing claims, Durban explores the creative ways that same-sex desiring and gender creative Haitians contend with anti-LGBTQI violence and ongoing foreign intervention. Compelling and thought-provoking, The Sexual Politics of Empire examines LGBTQI life in contemporary Haiti against the backdrop of American imperialism and intervention.